Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 19515607 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Material sample", "BasisOfRecord is Specimen" ] }, "Country is Mexico", "OccurrenceStatus is Present" ] } The dataset includes 19515607 records from 2674 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0136910-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences